2018
DOI: 10.3390/nu10111706
|View full text |Cite
|
Sign up to set email alerts
|

Almond Allergy: An Overview on Prevalence, Thresholds, Regulations and Allergen Detection

Abstract: Food allergy has been on the increase for many years. The prevalence of allergy to different foods varies widely depending on type of food, frequency of consumption and geographic location. Data from the literature suggests that the prevalence of tree nut allergy is of the order of 1% in the general population. Almond is one such tree nut that is frequently eaten in many parts of the world and represents a potential allergenic hazard. Given the need to label products that contain allergens, a number of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 78 publications
0
21
1
Order By: Relevance
“…83 It was considered to be an almond allergen and called Pru du 2. 77,78,83 However, as for almond PR-10, we could not find any immunological characterization of almond PR-5. Thus, almond PR-5 may be an allergen because it has very high sequence identity with the peach allergen Pru p 2, 19,90 although immunological experiments or food challenging data are needed to confirm this.…”
Section: Almond Proteins That Are Called Allergens Without Immunologicontrasting
confidence: 69%
See 4 more Smart Citations
“…83 It was considered to be an almond allergen and called Pru du 2. 77,78,83 However, as for almond PR-10, we could not find any immunological characterization of almond PR-5. Thus, almond PR-5 may be an allergen because it has very high sequence identity with the peach allergen Pru p 2, 19,90 although immunological experiments or food challenging data are needed to confirm this.…”
Section: Almond Proteins That Are Called Allergens Without Immunologicontrasting
confidence: 69%
“…Pru du γ-conglutin Almond γ-conglutin was considered as an almond allergen 64,77,78 because it was reported that the N-terminal sequencing of a 45-kDa IgE binding protein resulted in a sequence of 25AA that had 40% identity with the 45-kDa mature γ-conglutin of white and narrow-leafed lupine. 64 To our knowledge, no additional information about this almond protein is available.…”
Section: Almond Allergens That Have Not Received Official Names From mentioning
confidence: 99%
See 3 more Smart Citations